Establishing objectives in clinical practice:What directions to follow? (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
Different or incompatible answers about therapeutic goals are found even among behavior analysts professionals. Some factors may contribute to divergences: multidetermination of behavior, multiple origins of behavior therapy, the recent rise of clinical behavior analytical literature, the analysis of individual subject, the discussion of establishment of therapeutic objectives is little explored in literature. Establishing objectives requires good interpretation of the behavior process, gives the therapist directions for, helps client motivation for change, gives more security to therapist and client and offers better parameters for therapeutic assessment. This work intends to develop reflections about clinical directions in a behavior-analytic approach and presents some analyses that can contribute to reduce divergences or incompatibilities. Clinical cases treated in the behavioral approach are presented to exemplify different directions for the same data.